Relating ethical leadership with work engagement: How workplace spirituality mediates? - Nosheen Adnan; Omar Khalid Bhatti; Waqas Farooq (Cogent Business & Management, 2020)
Throughout the 21st century, change has been a predominant theme in the workplace. Increased technology and globalization are two key contributors to the changing landscape. The costs of occupational health and well-being are increasingly being considered as sound "investments" as healthy and engaged employees yield direct economic benefits to the company. The concept of work engagement plays a vital role in this endeavour because engagement entails positive definitions of employee health and promotes the optimal functioning of employees within an organizational setting. The present article reviewed existing human resource management and leadership literature and then proposes a framework that links employee engagement, workplace spirituality and ethical leadership. Drawing on self-determination theory (SDT) that proffers workplace spirituality as an arbitrator in the relationship between employee work engagement and ethical leadership. A set of propositions that represent an empirically driven research agenda are presented.
Keywords: 650; work engagement; workplace spirituality; ethical leadership; self-determination theory; conceptualization; literature review